Ultra-Sensitive Flexible Pressure Sensor Based on Microstructured Electrode - Mengmeng Li (Sensors, 2020)
Flexible pressure sensors with a high sensitivity in the lower zone of a subtle-pressure regime has shown great potential in the fields of electronic skin, human−computer interaction, wearable devices, intelligent prosthesis, and medical health. Adding microstructures on the dielectric layer on a capacitive pressure sensor has become a common and effective approach to enhance the performance of flexible pressure sensors. Here, we propose a method to further dramatically increase the sensitivity by adding elastic pyramidal microstructures on one side of the electrode and using a thin layer of a dielectric in a capacitive sensor. The sensitivity of the proposed device has been improved from 3.1 to 70.6 kPa−1 compared to capacitive sensors having pyramidal microstructures in the same dimension on the dielectric layer. Moreover, a detection limit of 1 Pa was achieved. The finite element analysis performed based on electromechanical sequential coupling simulation for hyperelastic materials indicates that the microstructures on electrode are critical to achieve high sensitivity. The influence of the duty ratio of the micro-pyramids on the sensitivity of the sensor is analyzed by both simulation and experiment. The durability and robustness of the device was also demonstrated by pressure testing for 2000 cycles.